Genotype-induced changes in biophysical properties of frontal cortex lipid raft from APP/PS1 transgenic mice - Diaz, Mario L.; Fabelo, Noemi; Marin, Raquel (Frontiers in Physiology, 2012)
Alterations in the lipid composition of lipid rafts have been demonstrated both in human brain and transgenic mouse models, and it has been postulated that aberrant lipid composition in lipid rafts is partly responsible for neuronal degeneration. In order to assess the impact of lipid changes on lipid raft functional properties, we have aimed at determining relevant physicochemical modifications in lipid rafts purified from frontal cortex of wild type (WT) and APP/PS1 double transgenic mice. By means of steady-state fluorescence anisotropy analyses using two lipid soluble fluorescent probes, TMA-DPH (1-[(4-trimethyl-amino)phenyl]-6-phenyl-1,3,5-hexatriene) and DPH (1,6-diphenyl-1,3,5-hexatriene), we demonstrate that cortical lipid rafts from WT and APP/PS1 animals exhibit different biophysical behaviours, depending on genotype but also on age. Thus, aged APP/PS1 animals exhibited slightly more liquid-ordered lipid rafts than WT counterparts. Membrane microviscosity napp analyses demonstrate that WT lipid rafts are more fluid than APP/PS1 animals of similar age, both at the aqueous interface and hydrophobic core of the membrane. napp in APP/PS1 animals was higher for DPH than for TMA-DPH under similar experimental conditions, indicating that the internal core of the membrane is more viscous than the raft membrane at the aqueous interface. The most dramatic changes in biophysical properties of lipid rafts were observed when membrane cholesterol was depleted with methyl-beta-cyclodextrin. Overall, our results indicate that APP/PS1 genotype strongly affects physicochemical properties of lipid raft. Such alterations appear not to be homogeneous across the raft membrane axis, but rather are more prominent at the membrane plane. These changes correlate with aberrant proportions of sphingomyelin, cholesterol and saturated fatty acids, as well as polyunsaturated fatty acids, measured in lipid rafts from frontal cortex in this familial model of Alzheimer’ Disease.